Transnationalism and the Resistance from Below - Pant, Yadav Raj (NUTA Journal, 2019)
This research article focuses on the deciphering of the various facets of transnationalism thereby opening up the avenues for the discussion of the resistance from below. Whether or not the transnationalism would support the resistance from below or resist the resistance from below is the concern of debate. However, the result of transnationalism causes the cultural fluidity and the hybridity in every aspect of life- be it cultural, political or economic. When transnationalism is defined as the tool for the global capitalism, the resistance from below could be eroded and sidelined. There, the relations are not as clear as one expects them and not as opaque as we assume them to be.